O istocie radości w teologii i poezji średnio− wiecza. Wokół poematu Cleanness (tłum. D. Chabrajska) - BRZEZINSKI POTKAY, Monica; CHABRAJSKA, Dorota (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
For the Middle Ages, the best−known tradition concerning joy is that found in the love poetry of the troubadours and trouvères. Yet alongside this secular celebration of erotic joi developed a religious tradition which taught that God had created the human soul in His image and likeness in order to make it capable of sharing His joy. The soul as imago dei, as long as it avoided sin, would enjoy God fully after death in the beatific vision. Yet men and women could experience foretastes of beatific joy on earth whenever they expressed their divine nature in acts of love, particularly when they encountered a loving God in prayer and meditation, or when they lovingly joined together in marriage. The varied homiletic passages and Biblical exempla contained in the late fourteenth−century English poem Cleanness illustrate types of joy, beatific, mystical, and marital, all of which are natural to humans by virtue of their identity as images of God. In constructing his poem, the author of Cleanness draws on the medieval theology of divine joy as developed in the treatises of St. Augustine, the mystical works of Cistercian monks, and devotional and homiletic literature written by or for English laity. Lecture delivered at the international seminar “O radości – Of Joy” held by the the quarterly Ethos and the John Paul II Institute at the Catholic University of Lublin on 7 April 2011. The author thanks The Wendy and Emery Reves Center for International Studies, College of William and Mary (Williamsburg, Virginia, USA), for financial support of her participation in the seminar.